Dewey’s Social Philosophy - Shook, J. author. aut Link
VIII, 189 p.
Keywords: Dewey is known for education theories to promote democracy, but what is democracy for? His philosophy advanced democracy as education itself, reaching higher levels of social intelligence. Praising community or promoting rights doesn't get to the heart of Dewey's vision, which seeks everyone's good in a social life that is intelligently lived.